Asset-Based Community Development and Digital Technology Impact on MSMEs’ Sustainable Competitive Advantage - Baka, Laode; Dano, Muhammad Guntur; Umaremba, Muhammad Irzhan Sungkan (LifeSciFi, 2025)
This study aims to analyze the influence of product innovation, community asset-based development, and proactive marketing on sustainable competitive advantage by considering the moderating role of digital technology in micro, small, and medium enterprises in Muna Regency. This study used a quantitative approach with an explanatory research design and involved 214 respondents selected through purposive sampling. The research instrument was a closed-ended questionnaire with a five-point Likert scale, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that product innovation had a significant effect on proactive marketing, but did not have a direct effect on sustainable competitive advantage. Conversely, the effect of product innovation on sustainable competitive advantage was mediated by proactive marketing. In addition, community asset-based development was shown to have a positive effect on both proactive marketing and sustainable competitive advantage. Proactive marketing itself made a significant contribution to sustainable competitive advantage. Digital technology has a diverse moderating role, namely strengthening the relationship between community asset-based development and sustainable competitive advantage, but weakening the relationship between product innovation and sustainable competitive advantage, and not significantly affecting the relationship between proactive marketing and sustainable competitive advantage. These findings underscore the importance of integrating innovation, community, marketing, and digital technology into MSME strategies to build sustainable competitiveness amidst market dynamics.